An integrated genomic and transcriptomic survey of mucormycosis-causing fungi - Chibucos, Marcus C.; Soliman, Sameh; Gebremariam, Teclegiorgis; Lee, Hongkyu; Daugherty, Sean; Orvis, Joshua; Shetty, Amol C.; Crabtree, Jonathan; Hazen, Tracy H.; Etienne, Kizee A.; Kumari, Priti; O’Connor, Timothy D.; et al. (Nature communications, 2016)
Mucormycosis is a life-threatening infection caused by Mucorales fungi. Here we sequence 30 fungal genomes, and perform transcriptomics with three representative Rhizopus and Mucor strains and with human airway epithelial cells during fungal invasion, to reveal key host and fungal determinants contributing to pathogenesis. Analysis of the host transcriptional response to Mucorales reveals platelet-derived growth factor receptor B (PDGFRB) signaling as part of a core response to divergent pathogenic fungi; inhibition of PDGFRB reduces Mucorales-induced damage to host cells. The unique presence of CotH invasins in all invasive Mucorales, and the correlation between CotH gene copy number and clinical prevalence, are consistent with an important role for these proteins in mucormycosis pathogenesis. Our work provides insight into the evolution of this medically and economically important group of fungi, and identifies several molecular pathways that might be exploited as potential therapeutic targets. Fungi of the order Mucorales can cause life-threatening infections. Here, Chibucos et al . present genomic and transcriptomic analyses of a diverse set of Mucorales fungi, shedding light on their evolution and identifying potential therapeutic targets in the pathogens and the host.